"A droga da guerra às drogas" : a produção de necropolítica na cidade de Salvador por meio do sistema de justiça criminal - Gois, Emerson Santos (2024)
In this study, the general objective is to genealogically analyze the documentary discourses that fabricate/forge criminally the drug trafficker under the aegis of Law No. 11.343 of 2006 (Drug Law) in the city of Salvador/BA, and the specific objective is to problematize eugenics and necropolitics in the social and legal reality, reflecting on the fabrication of bodies worthy of death. Noting that the war on drugs is first and foremost a war on people, its practices being directed to discipline and elimination of bodies counterproductive to the model of what this policy establishes as truth, one tried to think how the devices of racial subjectivation structure the power relations, and how these mean the understanding of the black body. It was analyzed whether the practices related to documentary production of the current Brazilian drug policy align with what is constructed epistemologically in the scope of Human Rights as a human being, tracing to what extent certain bodies fit and are recognized as worthy of life, and deserve the maintenance of their existence, and which are the bodies framed as enemies, and which therefore must be eliminated and controlled through a negative action of the State (to make die). Methodologically, the research was structured in a qualitative way, using bibliographical and documentary data collection techniques. In the bibliographic field, the philosophical concepts of biopolitics by Foucault (1979) and necropolitics by Mbembe (2016) helped to build the theoretical path. In the documentary field, a discourse analysis was performed from 5 (five) legal processes, filed in Salvador/BA in the months of September and October 2023, and judged by the 1st Court of Narcotics of the Capital. The discourses revealed, along the chosen processes, allowed to bring out how the strategies of social control, put in course by the colonization, find in the prohibition of drugs a seductive way to continue to reproduce their structures of legitimation, in which the image of the black is subjectivated by eugenic symbols that mystify his existence as dangerous, creating a war fiction in which his body becomes totally expendable.